Accuracy of inpatient oxygen administration. Issue 12 (December 1989) - Jeffrey, A A; Ray, S; Douglas, N J
Abstract : The accuracy of supplemental oxygen delivery was assessed in two medical units. Only 90 of 206 patients (44%) were receiving oxygen as prescribed. The ward oxygen rotameters were inaccurate at normal clinical flow rates, the range of flows being delivered as a percentage of the indicated flow varying from 15% at 8 l/min to 40% at 1 and 2 l/min.